Universal features of the stick-slip dynamics of an intruder moving through a confined granular medium - Pugnaloni, Luis; Carlevaro, Manuel; Kozlowski, Ryan; Zheng, Hu; Kondic, Lou; Socolar, Joshua E. S. (My University, 2022)
Experiments and simulations of an intruder dragged by a spring through a two-dimensional annulus of granular material exhibit robust force fluctuations. At low packing fractions (φ < φ0), the intruder clears an open channel. Above φ0, stick-slip dynamics develop, with an average energy release that is independent of the particle-particle and particle-base friction coefficients but does depend on the width W of the annulus and the diameter D of the intruder. A simple model predicts the dependence of φ0 on W and D, allowing for a data collapse for the average energy release as a function of φ/φ0. These results pose challenges for theories of mechanical failure in amorphous materials.
Keywords: Stick-slip; Jamming; Granular materials